Challenges and Opportunities in Meeting the Needs of IKN Weapon Systems in the Era of Modern Weaponry Technologies - II. Aries A.; Y. H. Yogaswara; Lutfi Adin Affandi; Koerozadi Faizal Iman (CV. AFDIFAL MAJU BERKAH, 2023)
The relocation of Indonesia's capital city to East Kalimantan has implications for defense and security. This research analyzes the challenges and opportunities of fulfilling the main equipment of the National Capital Integrated Coastal Development (IKN) defense system in the era of modern weaponry technology. Through the Systematic Literature Review (SLR) method, the evolution of warfare from the first generation to the information and cyber era is analyzed in relation to IKN. The research also highlights the development of weaponry technology and its impact on the IKN transition, as well as the urgency of fulfilling modern defense equipment and integrating advanced technology. The results indicate that the relocation of IKN requires strategic adaptation to the evolution of warfare and the use of new technologies in defense. It is crucial to comprehensively fulfill the needs of defense equipment in the air, land, sea, and cyber domains to maintain the sovereignty and security of IKN. With the integration of advanced technology and wise planning, the relocation of IKN can be approached with thorough preparation and an effective defense system. In facing these complex dynamics, international collaboration efforts and adaptation of defense policies become important to respond to global challenges and generate appropriate solutions.